Nanobody-Based Probes for Subcellular Protein Identification and Visualization - de Beer, Marit A.; Giepmans, Ben N. G. (Frontiers in Cellular Neuroscience, 2020)
Understanding how building blocks of life contribute to physiology is greatly aided by protein identification and cellular localization. The two main labeling approaches developed over the past decades are labeling with antibodies such as immunoglobulins (IgGs) or use of genetically-encoded tags such as fluorescent proteins (FPs). However, IgGs are large proteins (150 kDa), which limits penetration depth and uncertainty of target position caused by up to ~25 nm distance of the label created by the targeting approach. Additionally, IgGs cannot be easily recombinant expressed because they consist of multiple independent translated chains. In the last decade single-chain antigen binding proteins are being explored in bioscience as a tool in revealing molecular identity and localization to overcome limitations by IgGs. These nanobodies have several potential benefits over routine applications. Because of their small size (15 kDa), nanobodies better penetrate during labeling procedures and improve resolution. Moreover, nanobodies cDNA can be fused genetically with FPs cDNA and expressed in cells for live-cell endogenous protein detection. Alternatively, the nanobodies may be purified from cellular system and used on other cells or tissues. Given the option to combine different modular domains for targeting (nanobodies), visualization by fluorescence light microscopy (LM) or electron microscopy (EM; based on enzymes) and purification becomes possible. Here, we present the current state of nanobody-based probes implementation in microscopy, including pitfalls and potential future opportunities.